2018
DOI: 10.1038/s41598-017-18643-w
|View full text |Cite
|
Sign up to set email alerts
|

The high concentration of progesterone is harmful for endometrial receptivity and decidualization

Abstract: Progesterone is required for the establishment and maintenance of mammalian pregnancy and widely used for conservative treatment of luteal phase deficiency in clinics. However, there are limited solid evidences available for the optimal timing and dose of progesterone therapy, especially for the possible adverse effects on implantation and decidualization when progesterone is administrated empirically. In our study, mouse models were used to examine effects of excess progesterone on embryo implantation and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 79 publications
3
34
0
1
Order By: Relevance
“…Immunohistochemistry was conducted as described previously [15]. In brief, paraffin sections were deparaffinized and rehydrated.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemistry was conducted as described previously [15]. In brief, paraffin sections were deparaffinized and rehydrated.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In brief, whole uteri were smashed in a liquid nitrogen and were then Thyroid hormone and embryo implantation N. Salleh et al placed immediately in PRO-PREP extraction solution (Intron, Seoul, South Korea). GAPDH (sc-25778) was used as a loading control in view that its level in the uterus was not affected by the changing levels of sexsteroids (Liang et al, 2018). After mixing with a loading dye, 35 mg proteins were loaded onto 12% SDS-PAGE gel.…”
Section: Protein Quantification By Western Blottingmentioning
confidence: 99%
“…The antibody dilution was 1:1000. GAPDH (sc-25778) was used as a loading control in view that its level in the uterus was not affected by the changing levels of sexsteroids (Liang et al, 2018). The membranes were washed three times in phosphate buffered saline (PBS), 5 min each, and were then incubated with horseradish peroxidase conjugated secondary antibody (Santa Cruz, USA), at a dilution of 1:5000, for 1 h. In order to visualize the protein bands, membranes were washed and subjected to Opti-4CN TM Substrate Kit (Bio-Rad).…”
Section: Protein Quantification By Western Blottingmentioning
confidence: 99%
“…Many studies have reported a signi cantly higher risk of adverse pregnancy outcomes in women with low serum progesterone during pregnancy (2)(3)(4)(5). Excess serum progesterone, on the other hand, was reported to signi cantly suppress expression levels of decidualization markers in a dose-dependent manner and compromise embryo decidualization (6).…”
Section: Introductionmentioning
confidence: 99%